Endocrine and Cognitive Adaptations to Cope with Stress in Immature Common Marmosets (Callithrix jacchus): Sex and Age Matter - Sousa, Maria Bernardete Cordeiro de; Galvão, Ana Cecília de Menezes; Sales, Carla Jéssica Rodrigues; Castro, Dijenaide Chaves de; Galvão-Coelho, Nicole Leite (Frontiers in Psychiatry, 2015)
Phenotypic sex differences in primates are associated with body differentiation during the early stages of life, expressed in both physiological and behavioral features. Hormones seem to play a pivotal role in creating a range of responses to meet environmental and social demands, resulting in better reactions to cope with challenges to survival and reproduction. Our studies on brain plasticity combine hormonal and behavioral approaches to investigate stress-coping mechanisms in nonhuman primates. Steroid hormones actively participate in neuroplasticity and steroids from both gonads and neurons seem to be involved in behavioral modulation in primates. Indirect evidence suggests the participation of sexual steroids in dimorphism of the stress response in common marmosets. This is an important experimental model in Psychiatry, since we found a dual profile for cortisol in the transition from infancy to puberty, with females showing higher levels that extend to adulthood. Immature males and females at 6, 9 and 12 months of age moved alone from the family group to a new cage, over a 21-day period, expressed distinct patterns of cortisol variation, depending on age, but similar in terms of range of variation between sexes. Additional evidence showed that during juvenile to sub-adult transition males buffered the HPA axis during chronic stress. However, animals under both acute and chronic stress performed poorly on spatial cognitive tests and evidence from the literature that they respond better to social tasks indicates that new approaches are necessary to take advantage of this experimental model. These findings increase the potential of also using this experimental model during development, such as in adolescence, and strengthen the importance of sex as a part of experimental protocols that study neuropsychiatric illnesses such as anxiety and mood disorders as well as associated therapeutics.